ROS changes evoked by the natural sweetener Rebaudioside a in a neuronal system - G. J. M. Afonso; J. B. Silva; R. M. Santos; L. M. Rosário; R. M. Quinta-Ferreira; M. E. Quinta-Ferreira (Energy Reports, 2020)
Current water treatment methods are unable to eliminate artificial sweeteners, which can lead to their accumulation in the environment. Due to this problem, natural sweeteners can be used instead, but it is important to understand their effects in biological systems. Rebaudioside A, one of the main components of stevia, causes an increase in both ROS and in FAD linked autofluorescence in hippocampal CA3 area. These effects may be due to the insulin-mimetic properties of steviol glycosides, with the results suggesting that they cause enhancements in glycolysis and in OXPHOS, with this metabolic pathway being the possible source of the rise in ROS. In excess, these molecules may cause damage to brain cells through oxidative stress. As leftovers from Stevia's purification process can be used as biomass, with applications ranging from energy production to fertilization, continuous accumulation in the environment should be avoided in order to prevent undesired effects in the ecosystem.
Keywords: 330; Autofluorescence; CA3; OXPHOS; Reactive oxygen species; Stevia; Steviol Glycosides